f(x)=-(x+2)²+2
f(0)=-(0+2)²+2 = ??
f(1)=-(1+2)²+2 = ??
f(2)=-(2+2)²+2 = ??
f(3)=-(3+2)²+2 = ??
f(4)=-(4+2)²+2 = ??
Helpp

Respuesta :

f(0)=-(0+2)²+2 = -1*(2)² + 2 = -4 + 2 = -2        y =-2
element of the set x = 0 attribute to an element of a set of y ( calculated y = -2 )
f(1)=-(1+2)²+2 = -1*(3)² + 2 = -9 + 2 = -7        y = -7
element of the set x = 1 attribute to an element of a set of y ( calculated y = -7 )
f(2)=-(2+2)²+2 = -1*(4)² + 2 = -16 + 2 = -14    y = -14
element of the set x = 2 attribute to an element of a set of y ( calculated y = -14 )
f(3)=-(3+2)²+2 = -1*(5)² + 2 = -25 + 2 = -23    y = -23
element of the set x = 3 attribute to an element of a set of y ( calculated y = -23 )
f(4)=-(4+2)²+2 = -1*(6)² + 2 = -36 + 2 = -34    y = -34
element of the set x = 4 attribute to an element of a set of y ( calculated y = -34 )

Answer:

f(0)=-(0+2)²+2 = -1*(2)² + 2 = -4 + 2 = -2        y =-2

element of the set x = 0 attribute to an element of a set of y ( calculated y = -2 )

f(1)=-(1+2)²+2 = -1*(3)² + 2 = -9 + 2 = -7        y = -7

element of the set x = 1 attribute to an element of a set of y ( calculated y = -7 )

f(2)=-(2+2)²+2 = -1*(4)² + 2 = -16 + 2 = -14    y = -14

element of the set x = 2 attribute to an element of a set of y ( calculated y = -14 )

f(3)=-(3+2)²+2 = -1*(5)² + 2 = -25 + 2 = -23    y = -23

element of the set x = 3 attribute to an element of a set of y ( calculated y = -23 )

f(4)=-(4+2)²+2 = -1*(6)² + 2 = -36 + 2 = -34    y = -34

element of the set x = 4 attribute to an element of a set of y ( calculated y = -34 )

ACCESS MORE